Transformasi Nilai-Nilai Pendidikan Islam Dalam Pembelajaran Pesantren - Mulyadi, Veri Ikra (Journal of Islamic Education and Learning, 2024)
This study aims to examine how the transformation of Islamic education values is carried out in the learning process within the pesantren environment. As a traditional Islamic educational institution, pesantren plays a central role in shaping students' character and spirituality through a value-based learning approach. In the era of globalization and the advancement of information technology, pesantren are required to transform Islamic education values to remain relevant to contemporary needs without losing the Islamic essence that serves as their foundation. The research method used in this study is qualitative, employing a case study approach in several pesantren in Indonesia. Data collection techniques include observation, in-depth interviews, and documentation. The findings indicate that the transformation of Islamic education values in pesantren occurs through three main approaches: (1) integration of classical and modern curricula, (2) utilization of technology in learning, and (3) instilling character values such as honesty, discipline, responsibility, and tolerance through role modeling and habituation. Additionally, pesantren adapt their teaching strategies to meet contemporary needs while maintaining their traditional identity.The implications of this transformation show that pesantren not only sustain their existence but also evolve into Islamic educational institutions that are responsive and relevant to modern challenges. In conclusion, the transformation of Islamic education values in pesantren learning is a dynamic process that combines tradition and innovation to achieve holistic and sustainable education.